Gestão escolar: uma análise sobre as escolas como organizações aprendentes - Rodrigues, Rafaela Evaristo Gomes (2024)
In the field of school management, we can identify how the dynamics of the processes involving administration at school occur. However, it is important to understand management as a construction process. Such plurality present in this management leads us to an understanding that there is a dynamic and that the management process is built through people and organizational daily life. However, the term school management also refers to management policy, so that social aspects are incorporated. It is worth noting that the practice of school management occurs dynamically, involving several actors. The fact is that how a school is administered goes beyond standards, it is a set of practices carried out based on the schools' own experiences. It is important to understand that the school is also a society and that within it there will be disputes and conflicts, which confirms the relationship between education and politics. Therefore, it is necessary to understand that the daily life of schools and institutional actors says a lot about politics. Therefore, the general objective is to investigate how management learning processes occur in a public school located in João Pessoa. To this, the specific objectives are the following: (I) Investigate the social and political context of education in João Pessoa; (II) Identify which School Management uses innovative/alternative learning practices in João Pessoa; (III) Analyze how these innovative school management practices take place; To study how management learning occurs in the school under study, the methodological path included semi-structured interviews with social actors. This research is part of the basic qualitative study. Furthermore, an analysis was carried out from an interpretive perspective, in addition to the observational phase in the field. The results revealed the presence of politics in the role of the manager, another point to be observed are the practices that add up and corroborate learning, as another result of this research is that management is built on a day-to day basis, in addition to flexibility and management autonomy for the learning process. Analyzing the school as a LO (Learning Organization) goes beyond what is covered in the literature and understands that learning is continuous within that environment.